Urban dog : propuesta de diseño para mitigar la soledad y falta de entrenamiento en perros con propietarios que carecen de tiempo (2019)
The increase of single-person households, the decision of young adults to postpone or not have children are some of the most relevant aspects in the transformation of Colombian families, this have led us to the appearance of interspecies families being this a cultural and social phenomenon in the new family composition in which these new families are made of individuals and pets; professional ambitions, the struggle for gender equality and the volatility of life in the city are some of the examples that have reduced the time spent with our pets, the loneliness of this animal is the most relevant problem, for which it is proposed from the design to reduce the loneliness of dogs with owners who lack of time to provide to their pets.